THE INFLUENCE OF TRAINING AND WORK DISCIPLINE ON THE PERFORMANCE OF PT EMPLOYEES. STATE ELECTRICITY COMPANY IN PANGKAJENNE SIDENRENG RAPPANG DISTRICT - Rahmawati, St.; Fadlina, Fadlina; Rahman, Usman (Universitas Ichsan Sidenreng Rappang, 2024)
This research aims to determine the effect of Training and Work Discipline on Employee Performance at the State Electricity Company in Pangkajenne Sidenreng Rappang, either partially or simultaneously. This research analyzes phenomena through collecting basic data, namely through statements that are tested through testing the validity and reliability of each statement item answered by the respondent. The method used in this research is a quantitative method with a Likert scale. The object of this research is Training and Work Discipline on Employee Performance. The hypothesis results from Training (X1) with tcount (6.410) ≥ ttable (2.000) so it is proven that the Training variable has a significant effect on employee performance, so at a 5% error level the hypothesis is stated as H02 rejected and Ha2 accepted. This means that Training has a significant effect on Employee Performance at, PT. Negara Electric Company in Pangkajenne Sidenreng Rappanghe results of the Work Discipline hypothesis (X2) with tcount (7.213) ≥ ttable (2.000) so it is proven that the Work Discipline variable has a significant effect on Employee Performance, so in error rate of 5% hypothesis is stated as H02 is rejected and Ha2 is accepted. This means that Work Discipline has a significant effect on Employee Performance at State Electric Company in Pangkajenne Sidenreng Rappang. Hypothesis results simultaneously show that Training (X1), Work Discipline (X2) have a positive and significant effect on Employee Performance (Y) 51.0%. while 49.0% of the results were influenced by other variables unknown in this study.